Frequent use of IGHV3-30-3 in SARS-CoV-2 neutralizing antibody responses - Pushparaj, Pradeepa; Nicoletto, Andrea; Castro Dopico, Xaquin; Sheward, Daniel J.; Kim, Sungyong; Ekström, Simon; Murrell, Ben; Corcoran, Martin; Karlsson Hedestam, Gunilla B. (Frontiers in Virology, 2023)
The antibody response to SARS-CoV-2 shows biased immunoglobulin heavy chain variable (IGHV) gene usage, allowing definition of genetic signatures for some classes of neutralizing antibodies. We investigated IGHV gene usage frequencies by sorting spike-specific single memory B cells from individuals infected with SARS-CoV-2 early in the pandemic. From two study participants and 703 spike-specific B cells, the most used genes were IGHV1-69, IGHV3-30-3, and IGHV3-30. Here, we focused on the IGHV3-30 group of genes and an IGHV3-30-3-using ultrapotent neutralizing monoclonal antibody, CAB-F52, which displayed broad neutralizing activity also in its germline-reverted form. IGHV3-30-3 is encoded by a region of the IGH locus that is highly variable at both the allelic and structural levels. Using personalized IG genotyping, we found that 4 of 14 study participants lacked the IGHV3-30-3 gene on both chromosomes, raising the question if homologous IGHV genes could substitute for IGHV3-30-3 in persons lacking this gene. In the context of CAB-F52, we found that none of the tested IGHV3-33 alleles, but several IGHV3-30 alleles could substitute for IGHV3-30-3, suggesting functional redundancy between the highly homologous IGHV3-30 and IGHV3-30-3 genes for this antibody.